Norms, normality and normalization: papers from the postgraduate summer school in German Studies, Nottingham, July 2013 - Uecker, Matthias (Nottingham ePrints, 2014)
A collection of 12 papers delivered at the DAAD Postgraduate Summer School in German Studies "Norms, Normality and Normalization".